DINÁMICA DE SEROCONVERSIÓN EN HEMBRAS BOVINAS POST ELIMINACIÓN DE ANIMALES PORTADORES DEL VIRUS DE LA DIARREA VIRAL BOVINA - Jayashi F., César (2005)
A study was conducted to determine the effect of culling BVDV carrier animals on the seroconversion against BVDV in the new generation of heifers from a dairy herd located in Arequipa, Peru. Blood samples were collected to 6-12 month old females in four sampling periods: January (n=73), June (n=48), October 2003 (n=48), and January 2004 (n=35) to evaluate their serological status against BVDV and to screen for carrier animals using the virus neutralization and antigen-capture ELISA tests, respectively. The prevalence of BVDV was 80.8 ± 9.0, 56.3 ± 14.0, 50.0 ± 14.2 and 22.9 ± 13.9% in the first, second, third and fourth sampling period, respectively. There were 2.7% (2/73) of carrier heifers in the group sampled in January 2003, and none in the subsequent sampling periods. The incidence of BVDV infection was 12/100 heifers per month from January 2003 till January 2004. The logistic regression test showed that culling of carrier animals in January 2003 reduced the risk of infection in subsequent months. In addition, age was a risk factor for VDVB infection in this group of animals. The results showed that BVDV infection is highly prevalent in herds having carrier animals, and that the culling of PI animals reduce the risk of infection in herd mates as indicated in the literature. The results also suggest that the control and eradication of BVDV in intensive management dairy herds may be possible by identifying and culling carrier animals and without vaccination but ensuring high level of biosecurity.